Integrating the Accounting Function into Cyber Risk Governance: A Proposed Organizational Framework to Strengthen Financial Information Protection in the Public Sector: Mengintegrasikan Fungsi Akuntansi ke dalam Tata Kelola Risiko Siber: Usulan Kerangka Kerja Organisasi untuk Memperkuat Perlindungan Informasi Keuangan di Sektor Publik - Assist. Prof. Dr. Ammar Ghazi Ibrahim Al-Ezzi (Indonesian Journal of Law and Economics Review, 2026)
General Background The rapid digital transformation in the public sector has increased reliance on electronic financial information systems, raising concerns about cybersecurity threats to financial data integrity. Specific Background Cyber risk governance has emerged as a strategic necessity, yet the organizational positioning of the accounting function within such frameworks remains unclear. Knowledge Gap Existing governance structures inadequately define the role of accounting in managing financially significant cyber risks, leading to institutional and structural misalignment. Aims This study aims to examine the integration of the accounting function into cyber risk governance and to propose an organizational framework that strengthens financial information protection. Results The findings reveal a significant organizational gap characterized by the absence of formal accounting roles, weak coordination between cybersecurity and financial policies, and limited involvement of accounting in risk assessment. Novelty The study introduces a multidimensional organizational framework that systematically integrates accounting into cyber risk governance through structural, functional, policy, and monitoring dimensions. Implications The proposed framework supports improved financial data security, enhanced transparency, and stronger accountability in public sector governance, contributing to more reliable financial reporting systems Keywords: Cyber Risk Governance, Accounting Integration, Public Sector Governance, Financial Information Security, Organizational Framework Key Findings Highlights Structural exclusion of accounting roles limits coordination in digital risk management Policy misalignment creates uncertainty in protecting governmental financial data Multidimensional framework enables stronger institutional alignment and oversight